Erdheim-Chester disease: a rare cause of bilateral renal artery stenosis, mimicking large vessel vasculitis. Issue 3 (15th March 2022) - Lakhani, Priyanka Mayur; Borysiewicz, Catherine; Mason, Justin
Abstract : A man in his 50s with resistant hypertension and history of Langerhans cell histiocytosis (LCH) was referred to rheumatology after suspicion of inflammatory arteritis was raised. This followed detection of bilateral renal artery stenosis during investigation for severe hypertension refractory to medical therapy. CT angiography revealed diffuse wall thickening of the abdominal aorta, in keeping with an aortitis. However, there was no serological or clinical evidence suggestive of a vasculitic process. Medical history included cranial diabetes insipidus, subclavian artery stenosis and spinal stenosis requiring surgery, over the course of 8 years. These findings led to consideration of Erdheim-Chester disease (ECD), a form of non-Langerhans cell histiocytosis, where there is abnormal proliferation of histiocytes which causes tissue fibrosis and sclerosis of the long bones. Subsequent plain radiographs of the long bones revealed appearances consistent with a diagnosis of ECD. Thus, a diagnosis of an LCH/ECD overlap syndrome was made.